The Impact of Climate Change on Tourism in Nepal: A Causality Analysis (Prithvi Academic Journal, 2025)
Tourism is one of the leading sectors contributing to the countries' economic growth worldwide. It requires the ideal weather conditions, but climate change can significantly affect this sector. This study examines the causal, long-run, and short-run relationship between climatic factors and tourism demand under the given economic conditions based on data from 1990 to 2021. The climatic variables are maximum temperature, rainfall, and CO2 emission, and the economic variables, the consumer price index (CPI), are studied based on data availability. The Autoregressive Distributed Lag model is applied to estimate the longrun and short-run relationships and to investigate the causality; the Granger-Causality test is used. The findings show that there is a long-run as well as shortrun relationship between the variables. The consumer price index (CPI) is the key factor for tourist arrivals in Nepal in the long and short run. The climatic variables (maximum temperature and rainfall) have a negative but insignificant impact on tourist arrivals. There is an association between the emission of carbon dioxide and tourist arrivals. Granger's causality test investigates the causality between rainfall, consumer price index, and tourist arrival, which is unidirectional. The causality between tourist arrival and carbon dioxide emission is unidirectional. Climate change weakens the tourism industry and may affect economic development. In the long run, this research can pioneer assessing climate change's economic and environmental impacts in the tourism sector based on sustainable developments.